A special sleeve bearing for aluminum silicon wire, preparation method and application thereof

By using cobalt-based heat-resistant alloy or 316L stainless steel as the substrate on the aluminum-silicon spool bearing bushings and covering the CoCrAlY/Y2O3-Si/SiC and CoCrAlY-YSZ composite coatings, the problem of poor wear and corrosion resistance of the bearing bushings is solved, and the long-term and stable service of the bearing bushings is achieved.

CN119332190BActive Publication Date: 2025-03-11ANHUI MA STEEL SURFACE TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411902223.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The bearing bushings of aluminum-silicon spools have poor wear resistance and corrosion resistance, and their lifespan is very short. The actual service life is extremely unstable. Some bearing bushings fail after less than one day they are on the line.

Method used

Cobalt-based heat-resistant alloy or 316L stainless steel is used as the substrate for the bearing bushing, covering the composite coating, including CoCrAlY/Y2O3-Si/SiC and CoCrAlY-YSZ coatings, the coating is deposited by ultrasonic flame spraying or laser cladding technology, and silicon-based resin is coated in the uncovered area.

Benefits of technology

It significantly improves the wear resistance and corrosion resistance of the bearing bushings, extends the service life, ensures that the actual service life of the bearing bushings is relatively stable, and avoids the crushing and excessive wear of the bearing bushings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119332190B_ABST
    Figure CN119332190B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of surface technology, and in particular to a shaft sleeve bearing bushing dedicated to aluminum silicon wire, a preparation method and an application thereof, wherein the wear-contacting part on the shaft sleeve bearing bushing substrate is covered with a composite coating, and other parts are coated with a silicon-based resin, the shaft sleeve bearing bushing substrate is a cobalt-based heat-resistant alloy or 316L stainless steel, and the composite coating material system of the wear-contacting part of the shaft sleeve is CoCrAlY / Y 2 O 3 ‑Si / SiC, coating thickness 0.4~1.0mm, the composite coating material system of the bearing wear part is CoCrAlY‑YSZ, coating thickness 0.5~1.5mm, this kind of high temperature resistant, corrosion resistant, wear resistant and fragmentation resistant shaft sleeve and bearing suitable for aluminum silicon wire, and has good lubricity at high temperature, can greatly reduce the wear of shaft sleeve and bearing, avoid the fragmentation of bearing, so as to further extend the service life of shaft sleeve and bearing, and ensure the actual service life of shaft sleeve and bearing is relatively stable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of surface technology, and in particular to a shaft sleeve and bearing shell special for aluminum silicon wire, a preparation method and application thereof. Background Art

[0002] Hot-dip aluminum silicon (AlSi) coatings are mainly used for applications that require formability, high temperature resistance, and heat reflection, such as automobile exhaust pipes, mufflers, engine heat shields, various heat exchangers, and photovoltaic solar cell substrates.

[0003] In the hot-dip AlSi coating production line (AlSi line for short), the AlSi pot is the part with the worst service conditions among the process equipment in the entire production line. This is because the temperature inside the aluminum-silicon plating pot (about 650-700℃) is high, and aluminum is more active than zinc. In the high-temperature molten state, it has a stronger corrosive effect on roller components immersed in the pot. The service life of the sleeves and bearings in the pot is only 2-4 days under the corrosion of high-temperature liquid molten aluminum-silicon. The production line cannot increase production and efficiency due to the need to frequently replace sleeves and bearings.

[0004] At present, the friction pairs of aluminum-silicon wire shaft sleeves and bearings can be divided into two categories according to the material: 1. Alloy sleeves with alloy bearings, which have poor wear and corrosion resistance and a very short service life; 2. Thermal spraying / laser cladding coating sleeves with ceramic bearings (typical structures such as Chinese invention patent application CN202111540512.3), which have relatively good wear and corrosion resistance and can serve for up to about 7 days. The main problem is that there is a large mismatch in thermal expansion coefficients between ceramic bearings and alloy bushings, which can easily cause shaking and ceramic bearing breakage during service (whether it is O-type, two-point or three-point, such problems exist), resulting in the actual service life of bearings and sleeves being extremely unstable, and some bearings and sleeves fail within less than 1 day of being online.

[0005] In view of the above-mentioned defects, the inventors of the present invention finally obtained the present invention after a long period of research and practice. Summary of the invention

[0006] The purpose of the present invention is to solve the problems that the current aluminum-silicon wire shaft sleeve and bearing have poor wear resistance and corrosion resistance, very short service life, extremely unstable actual service life, and some bearing sleeves and bushes fail within less than 1 day of being put into operation. A special shaft sleeve and bearing for aluminum-silicon wire, a preparation method and application thereof are provided.

[0007] In order to achieve the above-mentioned object, the present invention discloses a shaft sleeve bearing shell specially used for aluminum silicon wire, wherein the wear-contacting part on the shaft sleeve bearing shell substrate is covered with a composite coating, and other parts are coated with a silicon-based resin, the shaft sleeve bearing shell substrate is a cobalt-based heat-resistant alloy or 316L stainless steel, and the composite coating material system of the wear-contacting part of the shaft sleeve is CoCrAlY / Y 2 O 3-Si / SiC, coating thickness 0.4~1.0mm, the composite coating material system of the bearing bushing wear part is CoCrAlY-YSZ, coating thickness 0.5~1.5mm.

[0008] Because the temperature in the aluminum silicon wire pot (about 650-700℃) is high, and aluminum is more active than zinc, it has a strong corrosive effect on the sleeve and bearing immersed in the pot in the high-temperature molten state, so the base material of the bearing sleeve should be selected from a heat-resistant and corrosion-resistant alloy; the selection of the sleeve and bearing friction pair is very important, and it is one of the most important factors that determine the service life of the sleeve and bearing, but the selection of the friction pair is quite particular: first, the friction pair cannot react sustainably with molten Al and Si at high temperatures, second, the friction pair must withstand high temperatures of about 700℃ and still have a certain hardness and wear resistance at high temperatures, and third, the wear of the friction pair in the service environment should not be too large. After long-term practical exploration, the inventor found that Si / SiC and YSZ are a pair of friction pairs that meet the above conditions. Because the sleeve and bearing base material is a heat-resistant and corrosion-resistant alloy, if the Si / SiC-YSZ friction pair system is directly deposited on the substrate, it is easy to fail due to CTE mismatch at high temperatures, so a suitable transition layer is required to improve its CTE matching.

[0009] Metal-metal friction pairs and metal / metal ceramic-ceramic friction pairs usually suffer from severe adhesive wear at high temperatures, while ceramic-ceramic systems are more likely to suffer from extremely severe abrasive wear. The present invention adopts semiconductor / ceramic-ceramic friction pairs, which have significantly lighter adhesive wear. Si has good bonding, high-temperature lubricity and toughness, which can avoid the abrasive wear of pure ceramic-ceramic systems. SiC is filled in Si as a hard wear-resistant phase, which improves the wear resistance of Si / SiC. Therefore, Si / SiC and YSZ have relatively good service performance as friction pairs in aluminum silicon wires.

[0010] At present, the ceramic bearings on the market are usually assembled with pure ceramic tiles and metal tile seats at high temperature. However, the temperature of the aluminum silicon wire is significantly higher than that of the zinc pot, and the process operation range of the gap assembly is significantly narrower. Therefore, it is easy to fail prematurely due to "broken tiles" during actual use due to problems such as assembly gap and processing accuracy. The present invention directly uses spraying / laser technology to deposit the above composite coating on the sleeve and bearing, avoiding the above problems and ensuring the consistency of the sleeve and bearing life. According to the material of the covering coating and the requirements for the coating performance, the sleeve and bearing need to be prepared using a suitable process.

[0011] The present invention also discloses a method for preparing the above-mentioned shaft sleeve and bearing shell specially used for aluminum silicon wire, which comprises the following steps:

[0012] S1, using supersonic flame spraying technology or laser cladding technology to 2 O 3Raw material powder and Si / SiC raw material powder are deposited on the sleeve to form CoCrAlY / Y 2 O 3 -Si / SiC coating, using supersonic flame spraying, atmospheric plasma spraying technology or laser cladding technology to deposit CoCrAlY-YSZ coating on the bearing;

[0013] S2, spraying liquid silicon-based polymer precursor onto the shaft sleeve and bearing by brushing or liquid spraying, depositing it onto the position of the shaft sleeve and bearing not covered by the thermal spraying / laser cladding coating, and curing it in a high temperature environment of 200~400℃, so as to obtain heat-resistant and corrosion-resistant silicon-based resin.

[0014] In step S1, CoCrAlY / Y 2 O 3 The raw material powder is composed of CoCrAlY and Y 2 O 3 CoCrAlY and Y are prepared by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation. 2 O 3 The feed mass ratio is 5:1~50:1.

[0015] In the step S1, the Si / SiC raw material powder is prepared from Si and SiC by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation, and the mass ratio of Si to SiC is 20:1-1:20.

[0016] In the step S1, the CoCrAlY / YSZ raw material powder is prepared by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation of CoCrAlY and YSZ, and the mass ratio of CoCrAlY to YSZ is 5:1-50:1.

[0017] The invention also discloses the application of the above-mentioned shaft sleeve and bearing shell specially used for aluminum-silicon wire in a hot-dip AlSi coating production line.

[0018] The invention also discloses the application of the above-mentioned shaft sleeve and bearing shell dedicated for aluminum silicon wire in a hot-dip galvanizing or zinc alloy production line.

[0019] Compared with the prior art, the beneficial effect of the present invention is that the high temperature resistant, corrosion resistant, wear resistant and crack resistant shaft sleeve and bearing suitable for aluminum silicon wire in the present invention has good lubricity at high temperature, can greatly reduce the wear of the shaft sleeve and bearing, and avoid the cracking of the bearing, thereby further extending the service life of the shaft sleeve and bearing, and ensuring that the actual service life of the shaft sleeve and bearing is relatively stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 (a) is a morphology of the grinding ball after friction and wear between Example 1 and the YSZ grinding ball at room temperature (scale is 500 μm);

[0021] Figure 1(b) is a morphology of the grinding ball after friction and wear between Example 1 and the YSZ grinding ball at room temperature (scale is 200 μm);

[0022] Figure 2 (a) is a morphology of the grinding balls of Comparative Example 1 and YSZ grinding balls after friction and wear at room temperature (scale is 500 μm);

[0023] Figure 2 (b) is a morphology of the grinding balls of Comparative Example 1 and YSZ grinding balls after friction and wear at room temperature (scale is 200 μm);

[0024] Figure 3 (a) shows the results of Example 1 and Al 2 O 3 The morphology of the grinding ball after friction and wear at room temperature (scale is 500μm);

[0025] Figure 3 (b) shows the results of Example 1 and Al 2 O 3 The morphology of the grinding ball after friction and wear at room temperature (scale is 200μm);

[0026] Figure 4 The wear scar data of friction and wear between Example 1 and YSZ grinding ball at room temperature;

[0027] Figure 5 The wear scar data of the friction and wear of the comparative example 1 and the YSZ grinding ball at room temperature;

[0028] Figure 6 For Example 1 and Al 2 O 3 Data diagram of friction and wear scar of grinding balls at room temperature;

[0029] Figure 7 The comparison results of wear volume, half-height width and wear scar depth between Example 1 and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0030] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0031] Example 1

[0032] (1) CoCrAlY / Y were sprayed on 316L stainless steel sample plates using supersonic flame 2 O 3 and Si / SiC coatings, the HVOF spraying process parameters are shown in Table 1, and the coating thickness is 350 μm;

[0033] (2) Grind and polish the plate surface coating used in step (1) to a roughness of <Ra0.4μm。

[0034] Table 1 HVOF sprayed CoCrAlY / Y 2 O 3 And Si / SiC coating process parameter table

[0035]

[0036] Example 2

[0037] (1) Design the sleeve and bearing drawings according to the requirements of the AlSi test pot;

[0038] (2) Process the bearing sleeve blank according to the drawing;

[0039] (3) CoCrAlY / Y is sprayed on the sleeve in sequence using supersonic flame spraying technology. 2 O 3 and Si / SiC coating, the process parameters are shown in Table 1, the total coating thickness is 0.8 mm;

[0040] (4) CoCrAlY and YSZ coatings were sprayed on the bearing shells in sequence by atmospheric plasma spraying technology. The process parameters are shown in Table 2. The total coating thickness is 1.2 mm.

[0041] Table 2 Process parameters of plasma sprayed CoCrAlY and YSZ coatings

[0042]

[0043] (5) Finish the bushings and bearings according to the drawings;

[0044] (6) The silicone-based resin precursor is applied to the area of ​​the bushing that is not covered by the thermal spraying by brushing, and then placed in a heat treatment tank for 300°C × 2h, and cooled to room temperature in the furnace.

[0045] Comparative Example 1

[0046] After the cobalt-based alloy is cut into a specimen of a specified shape, the surface is ground and polished to a roughness of <Ra0.4μm。

[0047] Comparative Example 2

[0048] (1) Design the sleeve and bearing drawings according to the requirements of the AlSi test pot;

[0049] (2) Process the cobalt-based alloy into shaft sleeves and bearing shells according to the drawings.

[0050] Comparative Example 3

[0051] (1) Design the sleeve and bearing drawings according to the requirements of the AlSi test pot;

[0052] (2) Processing the cobalt-based alloy into a shaft sleeve according to the drawing;

[0053] (3) Process YSZ ceramic tiles according to drawings;

[0054] (4) Processing the cobalt-based alloy into a tile seat according to the drawing;

[0055] (5) Assemble the tile block in step (3) into the tile seat in step (4) at a specified temperature.

[0056] At room temperature, a φ6.35 mm YSZ ceramic grinding ball was used to reciprocately rub the samples in Example 1 and Comparative Example 1, with a friction stroke of 5 mm, a frequency of 10 Hz, a load of 10 N, and a time of 30 min; at room temperature, a φ6.35 mm Al 2 O 3 Ceramic grinding balls, reciprocating friction example 1, friction stroke 5 mm, frequency 10 Hz, load 10 N, time 30 min.

[0057] After friction and wear, optical microscope, 3D profilometer and other equipment were used to compare and observe the wear marks of the worn grinding balls and samples. The results are shown in Figures 1 (a) to 3 (b).

[0058] The results of reciprocating friction of the grinding balls of Example 1 and Comparative Example 1 by YSZ are analyzed: According to the characterization results of Figures 1(a), 1(b), 2(a), and 2(b), the longest distance of the wear surface of the grinding balls of Example 1 after wear is 0.88 mm, and the longest distance of the wear surface of the grinding balls of Comparative Example 1 is 1.01 mm, and the surface of the grinding balls of Comparative Example 1 is adhered with cobalt-based alloy, indicating that relatively obvious adhesive wear occurs; according to Figure 4 , Figure 5 The characterization results show that the deepest depth of the wear scar in Example 1 is 10.2 μm, and the deepest depth of the wear scar in Comparative Example 1 is 26.4 μm, and the wear scar depth is 2.59 times that of Example 1, indicating that the degree of wear in Comparative Example 1 is significantly greater than that in Example 1; Figure 7 According to the characterization results, the wear volume, half-height width and wear scar depth of Example 1 are significantly smaller than those of Comparative Example 1. In summary, the wear resistance of the friction pair of Example 1 is much better than that of Comparative Example 1.

[0059] Example 1: YSZ grinding ball and Al 2 O 3 Analysis of the results after reciprocating friction of the grinding balls: According to the characterization results of Figures 1(a), 1(b), 3(a), and 3(b), the longest wear distance of the YSZ grinding ball in Example 1 is 0.88 mm, and the longest wear distance of the Al grinding ball in Example 1 is 0.88 mm. 2 O 3 The longest distance of the grinding ball wear surface is 1.00mm, and there is a certain amount of Si-SiC adhering to the grinding ball surface, indicating that the Al 2 O3 There is also a certain amount of adhesive wear on the grinding wheel; according to Figure 4 , Figure 6 The characterization results show that the deepest wear scar of Example 1 and YSZ is 10.2 μm, and the deepest wear scar of Example 1 and Al 2 O 3 The deepest depth of the wear scar is 18.2 μm, indicating that the wear degree of the same coating is different when using different friction pairs. The wear degree of YSZ on the grinding ball is significantly less than that of Al. 2 O 3 For grinding balls; Figure 7 The characterization results show that the wear volume, half-height width and wear scar depth of the YSZ grinding ball in Example 1 are significantly smaller than those of the Al 2 O 3 Grinding balls. In summary, even if the same material is used, from the perspective of friction and wear results, it is necessary to select suitable grinding materials to obtain relatively good wear resistance. Therefore, the selection of friction pairs also requires creative work.

[0060] The shaft sleeves and bearings of Example 2 and Comparative Examples 2 and 3 were respectively installed in an AlSi experimental pot at a temperature of 650° C. to simulate the application of the shaft sleeves and bearings in an AlSi production line.

[0061] After 10 days of experiment, Example 2 ran relatively stably. After stopping the machine and taking out the bushings and bearings, they were cleaned and inspected. It was found that although the composite coating on the surface of the bushings and bearings was worn (wear amount <0.3mm, single side, the same below), the coating was still intact and had not failed, indicating that the service life of the bushings and bearings of Example 2 was >10 days. After 3 days of stable operation of Example 2, the sinking roller began to shake. After stopping the machine to take out the sleeve and bearing, the sleeve and bearing were cleaned and inspected, and it was found that the sleeve and bearing were severely worn. After measurement, the dimensions of the sleeve and bearing were reduced by 1.5~3mm at various locations. This was the fundamental cause of the shaking of the sinking roller; Example 3 only ran smoothly for about 3.5 days, and the sinking roller began to shake abnormally. After stopping the machine to take out the sleeve and bearing, the sleeve and bearing were cleaned and inspected, and it was found that the bearing was also broken. This was the fundamental cause of the abnormal shaking of the sinking roller. The sleeve wear of Example 3 was slightly better than that of Example 2, with a wear amount ranging from 1.0 to 1.2mm, but the surface condition of the sleeve was obviously worse than that of Example 2.

[0062] In summary, the shaft sleeve and bearing shell prepared by the method of the present invention are suitable for the aluminum silicon production line, which solves the problem of the non-wear resistance of the previous metal sleeve-metal shell system and the unstable service life of the metal sleeve-ceramic shell, and further improves the service life of the bearing shell and shaft sleeve, and the improvement effect is very obvious.

[0063] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalents may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A special sleeve bearing for aluminum silicon wire, characterized in that: The wearing parts on the bushing substrate are covered with a composite coating, and other parts are coated with a silicon-based resin. The substrate of the bushing is a cobalt-based heat-resistant alloy or 316L stainless steel. The composite coating material system of the bushing wearing parts is CoCrAlY / Y2O3-Si / SiC, and the coating thickness is 0.4~1.0mm. The composite coating material system of the bushing wearing parts is CoCrAlY-YSZ, and the coating thickness is 0.5~1.5mm.

2. A method for preparing a special sleeve and bearing for aluminum silicon wire as claimed in claim 1, characterized in that: The following steps are involved: S1, using supersonic flame spraying technology or laser cladding to deposit CoCrAlY / Y2O3 raw material powder and Si / SiC raw material powder on the sleeve to form a CoCrAlY / Y2O3-Si / SiC coating, and using supersonic flame spraying technology, atmospheric plasma spraying technology or laser cladding technology to deposit CoCrAlY-YSZ coating on the bearing shell; S2, depositing liquid silicon-based polymer precursor onto the position of the bushing and bearing not covered by the thermal spraying / laser cladding coating by brushing or liquid spraying, and curing it in a high temperature environment of 200~400℃ to obtain heat-resistant and corrosion-resistant silicon-based resin.

3. The method for preparing a special sleeve and bearing for aluminum silicon wire according to claim 2, characterized in that: In the step S1, the CoCrAlY / Y2O3 raw material powder is prepared from CoCrAlY and Y2O3 by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation, and the mass ratio of CoCrAlY to Y2O3 is 5:1-50:

1.

4. The method for preparing a special sleeve and bearing for aluminum silicon wire according to claim 2, characterized in that: In the step S1, the Si / SiC raw material powder is prepared from Si and SiC by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation, and the mass ratio of Si to SiC is 20:1-1:

20.

5. The method for preparing a special sleeve and bearing for aluminum silicon wire according to claim 2, characterized in that: In the step S1, the CoCrAlY / YSZ raw material powder is prepared by mechanical mixing, sintering-crushing or sintering-crushing-ball milling-spray granulation of CoCrAlY and YSZ, and the mass ratio of CoCrAlY to YSZ is 5:1-50:

1.

6. An application of the special sleeve and bearing for aluminum-silicon wire as claimed in claim 1 in a hot-dip AlSi coating production line.

7. An application of the special sleeve and bearing for aluminum silicon wire as claimed in claim 1 in a hot-dip galvanizing or zinc alloy production line.

Citation Information

Patent Citations

  • Aluminum-silicon roller bushing in continuous hot-dip aluminum-silicon plating unit and preparation method of aluminum-silicon roller bushing

    CN116265598A

  • Axle sleeve and bush for zinc plating pot roller and its making method

    CN101117978A

  • Fiber-reinforced explosion-proof pipe composite coating for boiler pipe heated surface and preparation thereof

    CN111876716A